Rhodium(II)-Catalyzed Formal [3 + 2] Cycloaddition of N‑Sulfonyl-1,2,3-triazoles with Isoxazoles: Entry to Polysubstituted 3‑Aminopyrroles - Lei, Xiaoqiang; Li, Longbo; He, Yu-Peng; Tang, Yefeng (Organic letters, 2015)
A novel rhodium(II)-catalyzed formal [3 + 2] cycloaddition of N-sulfonyl-1,2,3-triazoles with isoxazoles has been achieved that provides an efficient method for the synthesis of polysubstituted 3-aminopyrrole derivatives. An operationally simple one-pot synthesis of the titled compounds from terminal alkynes, tosyl azide, and isoxazoles was also developed. The presented reaction affords an illustrative example of employing 1,2,3-triazoles as the [2C]-component in relevant cycloaddition reactions.